Potential of Empty Fruit Bunch Clinker as a Support for Nickel and Cobalt Catalysts in Methane Dry Reforming: Waste to Wealth Approach - Cheng, C. K.; Han, Jie Chan (Elsevier Ltd, 2016)
The current work reports on the synthesis of 20 wt% Co/80 wt% EFB clinker and 20 wt% Ni/80 wt% EFB clinker catalysts via wet-impregnation technique, followed by various characterization techniques such as BET, XRD, XRF, TGA and FESEM. The BET specific surface area of 20 wt% Co/80 wt% EFB clinker and 20 wt%Ni /80 wt% EFB clinker catalyst were 3.85 m2/g and 3.88 m2/g, respectively. In addition, XRD diffractogram of EFB clinker showed two highest peaks at around 2θ = 27.2° and 31.5°, which can be attributed to CaO and K2O species, respectively. This finding was also consistent with XRF analysis where potassium (K) and calcium (Ca) were positively identified. Subsequently, methane dry reforming studies revealed that the average conversion of CH4 for both sets of catalysts was nearly similar at 80.0%. When reaction temperatures were varied, the activation energy over the Co-based catalyst was 124.4 kJ/mol while that for the reaction over the Ni-based catalyst was 113.0 kJ/mol. In addition, during 12 days of dry reforming reaction, the conversion of CH4 was relatively stable over both sets of catalysts indicative of stability of their properties.